Rancang Bangun Sistem Informasi Manajemen Sekolah Berbasis Web Menggunakan Framework NextJS untuk Pengelolaan Administrasi Akademik di SMK Islam Permatasari 2 Rumpin – Bogor - Ariel Valorie Simanjuntak; Keris Ahmad Muanjan; Moh. Torik; Sutriyono (CV. Shofanah Media Berkah, 2026)
SMK Islam Permatasari 2 Rumpin – Bogor still faces several obstacles in managing academic administration, such as manual delivery of school information, a non-digitalized New Student Admissions (PPDB) process, and management of student data, attendance, tuition payments, and lesson schedules that have not been integrated. These conditions cause the administration process to be less effective, risk recording errors, and complicate data retrieval. Therefore, this study aims to design and build a web-based School Management Information System using the Next.js Framework as a solution to support integrated academic administration management. The methods used in this study include observation, interviews, and literature studies as data collection techniques. The system development stages include needs analysis, system design using the Unified Modeling Language (UML), implementation using the Next.js Framework with a MySQL database, and testing using the Black Box Testing method. System evaluation was also conducted using the Before–After method and questionnaires were distributed to 19 respondents to determine the level of success of the system implementation. The results of the study indicate that all key system features, including the company profile website, online PPDB (School Registration), student data management, attendance, tuition payments, and class schedule management, operate according to user needs without any significant functional errors. The Before-After evaluation results indicate that the system facilitates academic administration compared to the previous manual process. Furthermore, the questionnaire results indicate that the majority of respondents gave a positive assessment of the system's ease of use and benefits. Therefore, the developed web-based School Management Information System is deemed suitable for implementation as a supporting tool for academic administration management at SMK Islam Permatasari 2 Rumpin, Bogor.